Transmissibility, hospitalization, and intensive care admissions due to omicron compared to delta variants of SARS-CoV-2 in Catalonia: A cohort study and ecological analysis - Català, Martí; Coma, Ermengol; Alonso, Sergio; Andrés, Cristina; Blanco, Ignacio; Antón, Andrés; Bordoy, Antoni E.; Cardona, Pere-Joan; Fina, Francesc; Martró, Elisa; Medina, Manuel; Mora, Núria; et al. (Frontiers in Public Health, 2022)
Purpose: We aim to compare the severity of infections between omicron and delta variants in 609.352 SARS-CoV-2 positive cases using local hospitalization, vaccination, and variants data from the Catalan Health Care System (which covers around 7.8 million people). Methods: We performed a substitution model to establish the increase in transmissibility of omicron using variant screening data from primary care practices (PCP) and hospital admissions. In addition, we used this data from PCP to establish the two periods when delta and omicron were respectively dominant (above 95% of cases). After that, we performed a population based cohort analysis to calculate the rates of hospital and intensive care unit (ICU) admissions for both periods and to estimate reduction in severity. Rate ratios (RR) and 95% confidence intervals (95%CI) were calculated, stratified by age and vaccination status. In a second analysis, the differential substitution model in primary care versus hospitals allowed us to obtain a population-level average change in severity. Results: We have included 48,874 cases during the Delta period and 560,658 during the Omicron period. During the delta period, on average, 3.8% of the detected cases required hospitalization for COVID-19. This percentage dropped to 0.9% with omicron (RR of 0.46 [95%CI: 0.43 to 0.49]). For ICU admissions, it dropped from 0.8% to 0.1% (RR 0.25 [95%CI: 0.21 to 0.28]). The proportion of cases hospitalized or admitted to ICU was lower in the vaccinated groups, independently of the variant. Omicron was associated with a reduction in risk of admission to hospital and ICU in all age and vaccination status strata. The differential substitution models showed an average RR between 0.19 and 0.50. Conclusion: Both independent methods show consistently an important decrease in severity for omicron relative to delta. The systematic reduction happens regardless of age. The severity is also reduced for non-vaccinated and vaccinated group, but always higher in the non-vaccinated population. This suggests an overall reduction in severity, which could be intrinsic to the omicron variant. The fact that the RR in ICU admission is systematically smaller than in hospitalization points in the same direction.